Pengaruh Kebiasaan Membaca dan Penguasaan Kosakata terhadap Pemahaman Membaca Siswa (Survei di SMK Jakarta Timur) - Rosi Novayani Siregar (Deiksis, 2017)
The perposes of research are to find 1) The Effects of Reading Habit and Vocabulary Mastery Collaboratively Towards Student’s Reading Comprehension Skills. 2). The Effects of Reading Habit Towards Student’s Reading Comprehension Skills. 3). The Effects of Vocabulary Mastery Towards Student’s Reading comprehension skills. The research methodology that employed is Explanatory Survey Method and technique of data analysis that used in this research is regression analysis model.  The effect of independent variabel to dependent variabel. The statistic test used t-test and data analysis used correlation technique and multiple regression. The total sample of this research followed by 90 students.   Key word : Learning Model, Reading Habit, Student’s Descriptive Writing Skill